2011
DOI: 10.1016/j.molcel.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Dot1 and Histone H3K79 Methylation in Natural Telomeric and HM Silencing

Abstract: The expression of genes that reside near telomeres is attenuated through telomere position-effect variegation (TPEV). Using a URA3 reporter located at TEL-VIIL of S. cerevisiae, it was demonstrated that the disruptor of telomeric silencing-1 (Dot1) regulates TPEV by catalyzing the methylation of H3K79. URA3 was also used as a reporter to demonstrate that H3K79 methylation is required for HM silencing. Surprisingly, a genome-wide expression analysis of mutants defective in H3K79 methylation patterns indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
130
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 40 publications
(66 reference statements)
9
130
1
Order By: Relevance
“…For example, DOT1, SWI4, and ARD1, all of which abrogate H3K79 methylation, had been implicated in telomeric silencing, as assayed by the URA3 reporter at artificial telomeres. However, transcription of native genes at telomeres, as measured by microarray analysis, revealed little change in expression level in a dot1 mutant and other mutants proposed to disrupt H3K79 methylation (Takahashi et al 2011). Subsequent interrogation of the URA3 reporter found that dot1 and other mutants are actually differentially sensitized to the drug 5-FOA used to monitor URA3 expression (Rossmann et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DOT1, SWI4, and ARD1, all of which abrogate H3K79 methylation, had been implicated in telomeric silencing, as assayed by the URA3 reporter at artificial telomeres. However, transcription of native genes at telomeres, as measured by microarray analysis, revealed little change in expression level in a dot1 mutant and other mutants proposed to disrupt H3K79 methylation (Takahashi et al 2011). Subsequent interrogation of the URA3 reporter found that dot1 and other mutants are actually differentially sensitized to the drug 5-FOA used to monitor URA3 expression (Rossmann et al 2011).…”
mentioning
confidence: 99%
“…Additionally, some Y9 elements are transcribed, a fact that is inconsistent with Sir protein-mediated repression of all Y9 elements (Fourel et al 1999;Pryde and Louis 1999). In addition to these discrepancies, metabolic reporters are not biologically neutral, and some complexity regarding these reporters has emerged (Rossmann et al 2011;Takahashi et al 2011). For example, DOT1, SWI4, and ARD1, all of which abrogate H3K79 methylation, had been implicated in telomeric silencing, as assayed by the URA3 reporter at artificial telomeres.…”
mentioning
confidence: 99%
“…It was originally identified as a high copy disruptor of telomeric silencing in Saccharomyces cerevisiae (10). Two recent studies have demonstrated that the role of Dot1 in heterochromatin gene silencing might be overestimated in the original URA3 telomere silencing reporter assays in yeast (11,12). Nevertheless, Dot1 participates in heterochromatin formation through competing with Sir3 for a binding site on histone H4 (13).…”
mentioning
confidence: 99%
“…1 are metabolic in nature and Gdh1 is a metabolic protein, we further evaluated Gdh1's role in silencing through independent assays. Recent studies showed that 5-FOA-based telomeric silencing assays could give false-positive results for mutants that elevate ribonucleotide reductase (RNR) activities (37,38). One way to eliminate the confounding effect is to inhibit RNR activity with 10 mM hydroxyurea (HU) (37).…”
Section: Gdh1 Regulates Recruitment Of Sir Proteins To Silent Chromatmentioning
confidence: 99%